'An Imagist in Amber': Hart Crane's Early Publications and Greenwich Village. (11th March 2019) - Bratton, Francesca
Abstract: Examining Hart Crane's engagements with his editors and magazine publishers enables a reappraisal of his poetry and its critical reception. This reassessment pioneers an author study through methodologies associated with periodical studies with a close focus on the early stages of Crane's career, highlighting developments that were prompted by his reading of contemporaneous experiments in 'post-Decadence' in Greenwich Village journals of the late 1910s. This article examines the influence on his poetry of their particular brand of 'post-Decadent' modernism by looking at the shift from Crane's imitative efforts in fin-de-siècle poetics with 'C33' ( Bruno's Weekly ) and 'Carmen de Boheme' ( Bruno's Bohemia ) to later publications 'Echoes' and 'Modern Craft' in The Pagan that showcased his 'yellow book sympathies' using Imagistic forms, revealing Crane to be an 'Imagist in amber' (in Genevieve Taggard's suggestive phrase). Crane distanced himself from Village journals in 1919, and this article posits that this move marked an aesthetic shift from the sincere experiments in 'post-Decadence' and Imagism that characterize his early verse to the cosmopolitan, 'machine age' aesthetic of his later work. Finally, this article demonstrates how patterns established in his immediate reception are reproduced in later criticism – and may even explain his relative critical neglect. For his contemporary reviewers, who set the tone of his reception, he never quite escaped his association with Greenwich Village post-Decadence.